Effects of Pilates on strength of respiratory muscles in obese adolescents: a randomized controlled trial - Shah, Vidhi S.; Parab, Mansi; Patel, Jahanvi T.; Varunkar, Atul (International Journal of Contemporary Pediatrics, 2025)
Background: Childhood obesity is a significant risk factor for adult obesity, as well as a higher chance of death and impairment later in life. Increased obesity may compromise the function of the respiratory muscles. The main objective is to study the effects of Pilates on strength of respiratory muscles in obese adolescents. Methods: A randomized controlled trial (RCT) was conducted with 30 (12-19 years) obese adolescents. Participants were randomly allocated into Pilates group and conventional group using the envelop method. Both the groups received intervention for 5 days a week for 4 weeks. They were assessed pre and post intervention for respiratory muscle strength using surface electromyography. Results: The result showed that there is significant difference within the groups for Pilates and conventional group [spontaneous activity (SPA), quotient of motor unit action potential (QMUP) and maximum voluntary activity (MVA) (p=0.0001)]. There was also significant difference between the groups for respiratory muscle strength [p=0.0077 for spa, 0.0136 for QMUP and 0.0488 for MVA]. Conclusions: The present study concludes that there was significant improvement in the strength of the respiratory muscles in Pilates group when measured using the surface electromyography. Clinically, the Pilates group has better improvement on the strength.